2013
DOI: 10.1161/strokeaha.113.002604
|View full text |Cite
|
Sign up to set email alerts
|

Age and Ethnic Disparities in Incidence of Stroke Over Time

Abstract: Background and Purpose-Data on continuous monitoring of stroke risk among different age and ethnic groups are lacking.We aimed to investigate age and ethnic disparities in stroke incidence over time from an inner-city population-based stroke register. Methods-Trends in stroke incidence and before-stroke risk factors were investigated with the South London StrokeRegister, a population-based register covering a multiethnic population of 357 308 inhabitants. Age-, ethnicity-, and sexspecific incidence rates with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
72
6
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 30 publications
(54 reference statements)
7
72
6
3
Order By: Relevance
“…For instance, data from the United States have shown that stroke incidences have declined in the White but not in the Black population. 9,15 Similar findings were reported by the South London Stroke registry, 14 and a recent systematic review of studies from 19 countries and 5 continents found that stroke is more common in men but more severe, with high 1-month case-fatality rate, in women. 16 In addition to remaining widespread disparities and inequalities in stroke morbidity and mortality, rapidly aging populations are expected to further increase the absolute disease burden of stroke in the future.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…For instance, data from the United States have shown that stroke incidences have declined in the White but not in the Black population. 9,15 Similar findings were reported by the South London Stroke registry, 14 and a recent systematic review of studies from 19 countries and 5 continents found that stroke is more common in men but more severe, with high 1-month case-fatality rate, in women. 16 In addition to remaining widespread disparities and inequalities in stroke morbidity and mortality, rapidly aging populations are expected to further increase the absolute disease burden of stroke in the future.…”
supporting
confidence: 74%
“…Although these findings are consistent with research from other, mostly Western countries, our study uncovers these differences for the first time in a large mixedethnicity Asian population. 14,29 We also identified adverse trends in the younger population, particularly with regards to stroke incidence rates. Similar observations have been made in some western countries and have also been reported from the Global Burden of Disease Study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of a first ever stroke was taken from the study by Wang et al, 345 using the incidence rates in the white ethnicity group (approximately 99% of participants randomised to the CVD risk trial in the Healthlines study were of white ethnicity). Incidence rates were split into male and female rates using data from the same study.…”
Section: Incidence Of Fatal and Non-fatal Strokementioning
confidence: 99%
“…Previous studies on blacks have been conducted in multiethnic population 9,10 and have shown that overtime, stroke incidence reduced in white group but not in black group. In these multiracial populations, socioeconomic status discrepancy 12 and sustained inequalities in risk 11 may partly account for the observed ethnic differences.…”
Section: Strokementioning
confidence: 99%